2009
DOI: 10.1111/j.1600-065x.2009.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

PSGL‐1 function in immunity and steady state homeostasis

Abstract: The substantial importance of P-selectin glycoprotein ligand 1 (PSGL-1) in leukocyte trafficking has continued to emerge beyond its initial identification as a selectin ligand. PSGL-1 seemed to be a relatively simple molecule with an extracellular mucin domain extended as a flexible rod, teleologically consistent with its primary role in tethering leukocytes to endothelial selectins. The rolling interaction between leukocyte and endothelium mediated by this selectin-PSGL-1 interaction requires branched O-glyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
140
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 259 publications
(440 reference statements)
0
140
0
1
Order By: Relevance
“…5B). Moreover, two other key glycosyltransferases, b1,4GalT and FucT7, which were shown previously to be involved in the biosynthesis of sLe x motifs on activated T cells (27), were also found to be upregulated on SnL + Teffs (Fig. 5B).…”
Section: Upregulation Of Snl On Cd4 + T Cells Is Associated With Incrmentioning
confidence: 81%
See 2 more Smart Citations
“…5B). Moreover, two other key glycosyltransferases, b1,4GalT and FucT7, which were shown previously to be involved in the biosynthesis of sLe x motifs on activated T cells (27), were also found to be upregulated on SnL + Teffs (Fig. 5B).…”
Section: Upregulation Of Snl On Cd4 + T Cells Is Associated With Incrmentioning
confidence: 81%
“…As CD43 and PSGL-1 are major carriers of O-glycans on T cells (26,27), the failure to see reduced Sn-Fc binding to T cells lacking these glycoproteins suggested that O-glycans were not required for SnL expression. We investigated the nature of carbohydrate structures involved in Sn binding further using inhibitors of N-and Oglycan biosynthesis.…”
Section: Snl Requires N-linked Glycan Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, core 2 O-glycans decorated with the tetrasaccharide sialyl Lewis X are critical for mediating the calcium-dependent interaction between selectins and their corresponding ligands (27,28). Furthermore, a variety of molecules can serve as functional P-and E-selectin ligands, including P-selectin glycoprotein ligand-1 (PSGL-1), E-selectin ligand-1 (ESL-1), CD44, and perhaps more yet unidentified glycoproteins (29)(30)(31). Thus, the generation of functional ligands for P-and/or E-selectin on CD8 + T cells likely requires both the expression and appropriate glycosylation of a number of different cell surface proteins.…”
Section: Introductionmentioning
confidence: 99%
“…human scavenger receptor class B, member 2 (SCARB2), also known as lysosomal integral membrane protein 2 (LIMP-2) or CD36b like-2; and P-selectin glycoprotein ligand-1 (PSGL-1), also known as CD162 [9][10][11]. SCARB2 is expressed in most cell types, whereas PSGL-1 is limited to blood cells and endothelial cells, suggesting a distinct role for these two receptors in the pathogenesis of EV71 infection in vivo [12]. An important physiological function of SCARB2 is to transport acid b-glucosidase 1 (GBA1; also known as b-glucocerebrosidase), thereby supporting glycolipid metabolism [13].…”
Section: Introductionmentioning
confidence: 99%